The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2dt00080f
|View full text |Cite
|
Sign up to set email alerts
|

A dual-ratiometric optical thermometry based on Sr2LaF7:Er3+ crystal-implanted pliable fibers

Abstract: Sr2(La1-xErx)F7/polyacrylonitrile composite fibers with special pliability and excellent crystal dispersibility have been fabricated, which provide the smaller size and appropriate temperature sensitivity. Up-conversion emission shows quadratic dependence of the photoluminescence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…9,10 However, the optical thermometers based on the TCLs of rare-earth ions possess low relative sensitivity (S r ) triggered by the small energy band gap of TCLs (200 ≤ ΔE ≤ 2000 cm −1 ). 11,12 For the purpose of addressing this issue, researchers proposed a new route, namely, using the FIR technique to deal with the temperature-dependent emission intensities of non-TCLs of luminescent compounds. To date, some compounds, such as BaTiO 3 :Er 3+ /Ho 3+ /Yb 3+ , La 3 Li 3 W 2 O 12 :Eu 3+ /Mn 4+ , Na 5 Y 9 F 32 :Ce 3+ /Tb 3+ , YVO 4 :Eu 3+ / Nd 3+ , LaGaO 3 :Cr 3+ /Nd 3+ , and Ca 14 Al 10 Zn 6 O 35 :Ti 4+ / Eu 3+ , 13−18 with good thermometric properties, in which the non-TCLs are used, have been developed to realize contactless temperature sensing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 However, the optical thermometers based on the TCLs of rare-earth ions possess low relative sensitivity (S r ) triggered by the small energy band gap of TCLs (200 ≤ ΔE ≤ 2000 cm −1 ). 11,12 For the purpose of addressing this issue, researchers proposed a new route, namely, using the FIR technique to deal with the temperature-dependent emission intensities of non-TCLs of luminescent compounds. To date, some compounds, such as BaTiO 3 :Er 3+ /Ho 3+ /Yb 3+ , La 3 Li 3 W 2 O 12 :Eu 3+ /Mn 4+ , Na 5 Y 9 F 32 :Ce 3+ /Tb 3+ , YVO 4 :Eu 3+ / Nd 3+ , LaGaO 3 :Cr 3+ /Nd 3+ , and Ca 14 Al 10 Zn 6 O 35 :Ti 4+ / Eu 3+ , 13−18 with good thermometric properties, in which the non-TCLs are used, have been developed to realize contactless temperature sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, temperature monitoring with high sensitivity and resolution is very necessary. Compared with the conventional contacted thermometers, a lot of attention has been attracted by luminescence thermometers, which utilize temperature-associated fluorescence characteristics, such as fluorescence intensity ratio (FIR), band position, decay time, full width at half-maximum of emission band, etc., of luminescent materials because of their advantages of rapid response, high accuracy/resolution, and contactless characteristic. , Particularly, by adopting the FIR technique, optical thermometry is extensively adopted, in which the temperature-related emission intensities of thermally coupled levels (TCLs) of rare-earth ions are investigated. , Fu et al revealed that the thermometric properties of rare-earth ions, which were based on their TCLs, can be adjusted by controlling the excitation wavelength and utilizing tridoping engineering. , However, the optical thermometers based on the TCLs of rare-earth ions possess low relative sensitivity ( S r ) triggered by the small energy band gap of TCLs (200 ≤ Δ E ≤ 2000 cm –1 ). , For the purpose of addressing this issue, researchers proposed a new route, namely, using the FIR technique to deal with the temperature-dependent emission intensities of non-TCLs of luminescent compounds. To date, some compounds, such as BaTiO 3 :Er 3+ /Ho 3+ /Yb 3+ , La 3 Li 3 W 2 O 12 :Eu 3+ /Mn 4+ , Na 5 Y 9 F 32 :Ce 3+ /Tb 3+ , YVO 4 :Eu 3+ /Nd 3+ , LaGaO 3 :Cr 3+ /Nd 3+ , and Ca 14 Al 10 Zn 6 O 35 :Ti 4+ /Eu 3+ , with good thermometric properties, in which the non-TCLs are used, have been developed to realize contactless temperature sensing.…”
Section: Introductionmentioning
confidence: 99%